ON THE DIRECTIVITY OF DISPERSIVE TSUNAMI WAVES EXCITED BY PISTON-TYPE AND TRAVELING-WAVE SEA-FLOOR MOTION - Nosov M.A. (My University, 1998)
A linear potential theory was used for a comparative analysis of tsunami waves excited by piston-type and traveling sea-floor displacements. It is shown that the parameters of these waves depend considerably on the type of bottom motion, even though the residual displacements may be identical.